Implikasi Normatif Pengaturan Kecerdasan Buatan (AI) dalam Diagnosis Medis di Indonesia - Ami Hartati Puji Raya; Fathurrahman; Rahmad Hidayah; Khairunisyah (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2026)
The rapid development of artificial intelligence (AI) in healthcare offers significant potential to improve diagnostic accuracy while simultaneously raising normative challenges concerning legal certainty, ethics, and patient protection. This study aims to analyze the normative implications of AI regulation in medical diagnosis in Indonesia, highlighting regulatory weaknesses and proposing an ideal regulatory model. The research employed normative legal methods using statutory, historical, and conceptual approaches, supported by analysis through systematic, grammatical, and teleological interpretation of legal texts and academic literature. The findings indicate that AI regulation in Indonesia remains fragmented across several laws without a specific comprehensive framework, leading to legal liability uncertainty, weak patient data protection, and violations of informed consent principles. The results further suggest that the ideal regulatory model for Indonesia is a specialized risk-based regulation integrating health law, medical ethics, data protection, algorithmic transparency, and AI certification mechanisms under dedicated oversight. In conclusion, this research contributes theoretically by enriching the discourse on health and technology law, and practically by offering policy recommendations for establishing a fair, adaptive, and internationally aligned AI regulatory framework for medical diagnostics in Indonesia.